2011
DOI: 10.1902/jop.2011.110012
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Concentrations in Blood and Gingival Crevicular Fluid After Systemic Administration

Abstract: Background-Azithromycin is a macrolide antibiotic that is active against several periodontal pathogens. Macrolides are taken up and concentrated inside gingival fibroblasts, which could influence their pharmacokinetics. This study tested the hypothesis that steady-state levels of azithromycin are higher and more sustained in gingival crevicular fluid (GCF) than in serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
0
32
0
2
Order By: Relevance
“…Since A. actinomycetemcomitans exhibits strain-dependent differences in susceptibility to AZM, the effects of AZM on two different invasive strains were examined. Infected SG epithelial cells were treated with AZM concentrations similar to those found in blood (0.125 to 0.5 g/ml) and GCF (2 to 8 g/ml) (27). AZM produced dose-and time-dependent intraepithelial killing of both strains ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Since A. actinomycetemcomitans exhibits strain-dependent differences in susceptibility to AZM, the effects of AZM on two different invasive strains were examined. Infected SG epithelial cells were treated with AZM concentrations similar to those found in blood (0.125 to 0.5 g/ml) and GCF (2 to 8 g/ml) (27). AZM produced dose-and time-dependent intraepithelial killing of both strains ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…We identified the 1:27 dilutions as being of primary interest because they corresponded to levels obtained in gingival crevicular fluid (GCF) with the systemic use of these agents, i.e., 4, 10, and 8 g/ml for AMX, MTZ, and AZM, respectively (40)(41)(42). However, we also tested higher concentrations to examine whether they had increased efficacy.…”
Section: Susceptibility Of In Vitro Biofilms To Antibioticsmentioning
confidence: 99%
“…Lai et al measured steady-state levels of azithromycin in gingival crevicular fluid (GCF) and reported that the concentrations in GCF were higher and more sustained than those in serum. They suggested that the pharmacokinetic profiles of azithromycin are different in GCF and serum 6) . It was also reported that azithromycin attenuates acute and chronic tissue inflammation 4,5,9,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is known as an effective antibiotic in the treatment of odontogenic infections, 6) and the administration of a single large dose of azithromycin as front-loading achieves more rapid bacterial eradication and prophylaxis of postoperative infections including prevention of infective endocarditis 7,8) .…”
Section: Introductionmentioning
confidence: 99%